A mutual comparison of pregnancy outcomes between different conception modes: a propensity score matching based retrospective cohort study - Sun, Chang-Fa; Sheng, Jian-Zhong; Huang, He-Feng (Frontiers in Endocrinology, 2024)
Background Assisted reproductive technology (ART) has been reported to have negative effects on maternal and neonatal health. Ovulation induction (OI) was reported to be associated with alteration of epigenetic modification of mice embryos, and extinguishing the influence of ovulation induction and in vitro operations on maternal and neonatal health will bring benefits for reducing side effects. The present study aimed to determine whether ovulation induction alone and ART are associated with adverse pregnancy outcomes and whether ART could induce a higher risk than ovulation induction alone. Methods A total of 51,172 cases with singleton live birth between Jan 2016 and May 2019 at the International Peace Maternal and Child Health Hospital were included in this study. Conception modes documented during registration were classified into natural conception (NC), OI, and ART. Pregnancy outcomes of the three groups with balanced baseline characteristics by propensity score matching were compared. The relative risks of maternal and neonatal outcomes were calculated by logistic regression analysis. Results Compared with natural conception, infertility treatments are associated with gestational diabetes (OI: OR 1.72, 95% CI 1.31-2.27; ART: OR 1.67, 95% CI 1.26-2.20), preeclampsia/eclampsia (OI: OR 1.86, 95% CI 1.03-3.36; ART: OR 2.23, 95% CI 1.26-3.92). Even if gestational diabetes, gestational hypertension, and placental problems were adjusted, infertility treatments are associated with birth before 37 weeks (OI: OR 1.99, 95% CI 1.28-3.12; ART: OR 1.70, 95% CI 1.08-2.69), low birth weight (OI: OR 2.19, 95% CI 1.23-3.91; ART: OR 1.90, 95% CI 1.05-3.45), and SGA (OI: OR 2.42, 95% CI 1.20-4.87; ART: OR 2.56, 95% CI 1.28-5.11). ART but not OI is associated with a higher risk of birth before 34 weeks (OR:3.12, 95% CI 1.21-8.05). By comparing the OI group with the ART group, we only found that ART could induce a higher ratio of placental problems (5.0%, 26/518 vs 2.1%, 11/519, p<0.05). Conclusion Both OI and ART are associated with adverse pregnancy outcomes. ART induced comparable negative effects with OI on gestational complications, birth weight, and premature birth (<37 weeks). However, ART resulted in a higher risk of placental problems than group NC and OI. The incidence of birth before 34 weeks of gestation in the ART group tends to be higher than in the OI group, but not statistically significant. The side effects of ART may originate from OI.